KAJIAN JENIS DAN KELIMPAHAN REKRUTMEN KARANG DI PESISIR DESA KALIBUKBUK, SINGARAJA, BALI - Prasetia, I Nyoman Dodik (Bumi Lestari, 2013)
Abstract Kalibubuk coastal area is one nautical tourism destination in Buleleng regency. Higher levels used zone in coastal area especially coral reef ecosystem is not balanced with the study of the potential and carrying capacity of the environment, especially coral reefs. Coral settlement times to substrate is a critical phase that will determine the success of coral sexual reproduction. Success in forming coral reefs will determine the sustainability of coral reef ecosystems. The study was conducted in March and October 2011, aims to determine the pattern of spread of juvenile corals, species, abundance and survival of juvenile coral patterns and the physical, chemical, and biological factor. The study was conducted at a depth of 5 meters with 3 shelves on each research station research. A rack consists of 24 pieces of substrate with 4 different positions against the current. Juvenile corals were found to be composed of nine species of coral and 109 individuals. Juvenile corals are found at all stations in the study with the largest number of Station 3 as many as 59 individuals. Physical, chemical, and biological factor in Kalibukbuk relatively still support the growth and development of juvenile coral into coral colonies.
Keywords: Key words: juvenile, planula, recruitment, coral reef